Karakterisasi, Sifat Mekanik, dan Aplikasi Komposit Biofoam Studi Literatur - Muhajir, Muhamad; Reza Taufiqi Ivana; Taufik Abdullah Attamimi; Sri Muntiah Andriami; Uswatun Hasanah (RING ME, 2025)
Starch based biofoams have emerged as a sustainable alternative to conventional plastics, yet their performance varies significantly depending on formulation and processing methods. This study aims to comprehensively evaluate the relationship between raw material composition, production techniques, and functional properties of biofoams through an integrated analysis of ten recent formulations. The methodology involved a systematic review of experimental data derived from diverse production methods, including thermopressing, microbial fermentation, evaporative drying, freeze drying, and molding. Results reveal that banana peel and cassava starch and banana stem fiber biofoam offers an optimal balance of high tensile strength 43.86 MPa, low water absorption 16.91%, and moderate biodegradability 65.82%, making it ideal for dry food packaging. In contrast, bamboo powder biofoam exhibits exceptional water absorption 97.1%, suitable for horticultural substrates, while bamboo cellulose–starch composite demonstrates outstanding compressive strength 78.74 MPa and thermal stability 410.86 °C, indicating potential for lightweight structural applications. These findings underscore that biofoam design must be application-specific, providing evidence-based guidance for developing effective, sustainable materials tailored to real world needs.